Efek Aromaterapi Peppermint (Mentha arvensis L.) pada Penurunan Tekanan Darah - Tiya Nur Aini; Nur Mita; Niken Indriyanti (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2020)
Mint leaves (Mentha arvensis L.) are an example of a plant that can produce essential oils. The distinctive aroma of mint leaves provides a relaxing effect that affects the blood pressure of hypertensive patients. This study aims to look at the characteristics, patient response, and the effect of presenting peppermint aromatherapy to hypertensive patients at Puskesmas Mamburungan Tarakan. The research method used a quasy experimental research design with one group pretest and posttest design with a sample size of 20 people. The criteria for respondents who were the subject of the study were 50% of the sexes of women and men. The age with the highest proportion is 56-60 years old as much as 50%. The occupation with the highest proportion was housewives as much as 30%. The results of the study of the patient's response to aromatherapy preparations obtained the respondent's preferred level with a proportion of 90%. The effect of giving aromatherapy felt by the respondents was 75% fresh and 25% relaxed. Respondents would prefer it if peppermint oil was made in roll on dosage form (70%), compared to spray form (25%) and diffuser (5%). The results showed that there was an effect of peppermint aromatherapy on systolic blood pressure before the intervention took place with an average of 162,117 mmHg and after intervention it was 150,683 mmHg, diastolic blood pressure before intervention was 98.63 mmHg and after intervention it became 93.23 mmHg. The results of the descriptive research on peppermint aromatherapy are in line with the results of statistical analysis using the wilcoxon method and the paired sample t-test which has a p value of